Lithium Difluoro(dioxalato) Phosphate as an Electrolyte Additive for NMC811/Graphite Li-ion Pouch Cells. Issue 11 (1st November 2022) - Song, Wentao; Gauthier, Roby; Taskovic, Tina; Ouyang, Dongxu; Ingham, Harrison A.; Eldesoky, Ahmed; Azam, Saad M.; Zsoldos, Eniko S.; Deng, Zhe; Heino, Dylan H.; Geng, Chenxi; Sidebottom, Rowan; et al.
Abstract : Lithium difluoro(dioxalato)phosphate (LiDFDOP) has been systemically studied as an electrolyte additive singly and in combination with co-additives fluoroethylene carbonate (FEC) and vinylene carbonate (VC) in LiNi0.8 Mn0.1 Co0.1 O2 (NMC811)/artificial graphite (AG) pouch cells. Long-term cycling tests at room and elevated temperatures (20 °C, 40 °C, and 55 °C) with different upper cutoff voltages (4.06 V and 4.20 V) were performed. These results were combined with ultra-high precision coulometry (UHPC), ex-situ gas measurements, and automatic cell storage tests to reveal multiple aspects of cell performance. A density functional theory (DFT) calculation has also been performed and compared to formation data to reveal the mechanistic aspects of LiDFDOP reduction. Radar plots and a figure-of-merit (FOM) approach were further utilized to summarize results and rank additive and additive combination performance for the NMC811/AG cells. This work highlights an effective additive and suitable co-additives for use in NMC811/graphite cells and gives important insights for future electrolyte additive studies.